Analysis of Economic Recovery Policy Due to the Covid-19 Pandemic on the Productivity of Agricultural MSMEs And Small Traders in Bengkulu Province - Sumarni, Yenti (Budapest International Research and Critics University, 2022)
This study seeks to analyze government policies in relation to the economic recovery of the economy due to the COVID-19 pandemic, especially in the agricultural sector and MSMEs.The research method used in this study is qualitative research with a descriptive approach. The results of the study are that the National Economic Recovery Program (PEN) has a positive impact on the MSME sector during the COVID-19 pandemic as a policy step taken by the government to support the recovery of the national economy, especially the MSME sector which has a significant contribution. Policy stimulus for handling the MSME sector pandemic, which includes delays in principal and interest for MSMEs and UMi, subsidies for loan interest and UMi, tax incentives for MSMEs, guarantees for working capital loans for MSMEs, Regional Incentive Funds (DID), inclusion of banks and productive banpres are strategies for rescuing perpetrators. MSME efforts to be able to survive during the pandemic and increase MSME productivity and performance.